2014
DOI: 10.1016/j.nedt.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perspectives and suggestions on patient safety—Implications for developing the nursing education curriculum in Iran

Abstract: Background: Medication errors complicate up to half of inpatient stays and some have very serious consequences. To our knowledge, this is the first qualitative study of Iranian nursing students' perspectives of medication errors.Objectives: To describe nursing students' perspectives of the causes of medication errors.Design: Four focus groups were held with 24 nursing students from 4 different academic semesters in the nursing school in Tehran, between November 2011 and November 2012.Using a qualitative descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 61 publications
2
40
2
2
Order By: Relevance
“…In a study it has been reported that the most cited barriers from the perspectives of nurses include lack of appropriate educational environments (97.5%), shortages of nursing personnel (95.5%), funding deficits (92.5%), and lack of enough attention and support from management to patient education (82.1%), perspectives of administrators to teach patients (82.1%) (29). In other studies, these barriers have been reported alike (1,2,5,28).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…In a study it has been reported that the most cited barriers from the perspectives of nurses include lack of appropriate educational environments (97.5%), shortages of nursing personnel (95.5%), funding deficits (92.5%), and lack of enough attention and support from management to patient education (82.1%), perspectives of administrators to teach patients (82.1%) (29). In other studies, these barriers have been reported alike (1,2,5,28).…”
Section: Introductionsupporting
confidence: 51%
“…Various studies have shown significant relationships between educational degrees and employment duration of nurses with patients' mortality rates, disability rates, and unexpected events, incidence of infection, bed sores, and length of hospital stay, incidence of complications, patient dissatisfaction and the amount of considering ethical issues (18,(26)(27)(28). It is essential for nurses to be efficiently provided with the principles and techniques of teaching and learning processes for their educational role (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedding patient safety competencies in the current curriculum can be done by development of a particular course on patient safety wherein the emphasis is on the organization system and human factors, effective teamwork and optimal communication [6,10,23,24,[26][27][28]. Moreover, to appeal for a 'blame and shame free' culture it is essential to learn nursing students how to handle and prevent adverse events and to interference in reporting errors and coping with the fear of legal prosecution [3,6,9].…”
Section: Health Professional Education In Patient Safety Survey (H-pementioning
confidence: 99%
“…Patient safety is a part of daily practice, however, is not yet included in all nursing education curricula [3]. This results in a lack of knowledge and skills concerning patient safety [28]. Several authors state that nursing curricula therefore should be adjusted [10,26,27].…”
Section: Health Professional Education In Patient Safety Survey (H-pementioning
confidence: 99%